2012
DOI: 10.1038/mt.2011.294
|View full text |Cite
|
Sign up to set email alerts
|

Action and Reaction: The Biological Response to siRNA and Its Delivery Vehicles

Abstract: RNA interference (RNAi)-based therapeutics have significant potential for the treatment of human disease. Safe and effective delivery of RNA to target tissues remains a major barrier to realizing its clinical potential. Several factors can affect the in vivo performance of short interfering RNA (siRNA) delivery formulations, including siRNA sequence, structure, chemical modification, and delivery formulation. This review provides an introduction to the principles underlying the pharmacokinetics and pharmacodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
174
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(178 citation statements)
references
References 170 publications
(252 reference statements)
1
174
0
3
Order By: Relevance
“…Given the extensive data available that siRNAs can induce toll-like receptor (TLR)-mediated inflammatory responses in cells in vitro and in vivo 26 , we wished to determine the inflammatory profile of claudin-5 siRNA compared with both NT siRNA and a 2′OMe-modified claudin-5 siRNA. It has been shown that 2′OMe backbone modifications in even 2 residues of an siRNA can abrogate these effects and, in this regard, we designed an siRNA with 2 modifications in the sense strand of the siRNA 27 .…”
Section: Efficacy Of Systemic Administration Of Claudin-5 Sirnamentioning
confidence: 99%
“…Given the extensive data available that siRNAs can induce toll-like receptor (TLR)-mediated inflammatory responses in cells in vitro and in vivo 26 , we wished to determine the inflammatory profile of claudin-5 siRNA compared with both NT siRNA and a 2′OMe-modified claudin-5 siRNA. It has been shown that 2′OMe backbone modifications in even 2 residues of an siRNA can abrogate these effects and, in this regard, we designed an siRNA with 2 modifications in the sense strand of the siRNA 27 .…”
Section: Efficacy Of Systemic Administration Of Claudin-5 Sirnamentioning
confidence: 99%
“…1A, 2A, 3B and 4B). [43][44][45][46][47] In addition, they might be relatively unstable under physiological conditions due to loose complexation. Serum triggers polyplex aggregation and may diminish the difference of performance of the two sets of polyplexes under physiologically relevant conditions.…”
Section: Transfection Silencing and Cytotoxicitymentioning
confidence: 99%
“…One limitation of PEI as a transfection agent has been that both toxicity and delivery efficiency correlates with average molecular weight (MW) [23], and an average MW of 25kDa is generally considered the upper limit before the toxicity becomes problematic [11]. Several strategies have been devised to preserve the low toxicity of low-MW PEI but improve the delivery capability.…”
Section: Introductionmentioning
confidence: 99%